Análisis de las estrategias pedagógicas utilizadas por endocrinólogos expertos en educación en diabetes para la promoción de la salud y prevención de las complicaciones de esta enfermedad - Rossi Pérez, Ana Beatriz (Universidad Antonio Nariño, 2023)
the study of pedagogical strategies in health education is of interest due to the importance it has in the field of promoting lifestyle habits healthy and disease prevention. This is a qualitative research that Follow the case study. In-depth interviews were conducted with four physicians internists and endocrinologists with nearly 30 years of dedication to education in diabetes to find out A) Conceptions on health education, B) Strategies pedagogical and C) Competences that the professional must have to educate in health.